Pengaruh Dana Tabarru’ dan Klaim Terhadap Profitabilitas Pada Perusahaan Asuransi PT. Prudential Unit Syariah Periode 2011 – 2015 - Anton Hindardjo; Mansuri Mansuri (Jurnal Asy-Syukriyyah, 2016)
This study aimed to determine the effect of Tabarru 'and claim as a dependent variable and profit (Profit) as an independent. From here on test whether the effect on the dependent variable independent of either partial (individual) or simultaneously (overall). This type of research used is multiple regression analysis (multiple regression analysis). Based on the partial test (people) can be seen that there is a significant effect on the variable Tabarru '(X1) with sig amounting to 0,118 and (X2) value of 0.997, then based on the partial test (individual) is a real no significant effect on earnings ( profit). Based on the multiple linear regression analysis obtained R2 values of 0,981 (98.1%), which means that Tabarru 'and claims to have a real influence on the variable earnings.